Modelling the tactical difficulty of passes in soccer - Stöckl, M.; Cruz, D.; Duarte, R. (Proceedings of the 10th International Symposium on Computer Science in Sports (ISCSS), 2016)
A pass is an important action in soccer. Amongst other things, it allows moving the ball across the pitch quickly to create scoring opportunities and score goals. Passing performances are usually analyzed using descriptive measures such as number of passes or passing accuracy, however, neglecting the game context. This paper provides an approach to assess passes with respect to the tactical behavior of the participating teams. Results illustrate the application of the model by analyzing the passes played by players of different playing positions. Depending on the game context the players on different playing positions face different environments and, therefore, play passes of different tactical difficulty.